A critical analysis of foreign intervention in the Sikh Genocide of 1984 - Choudry, Anup Singh; Isabirye, Joel; Mbabazize, Mbabazi; Ojo, Olusola (Technium Social Sciences Journal, 2022)
This study critically discussed the role played by foreign actors in the Sikh genocide and the resulting violence of 1984. A review of literature established a dearth of relevant literature on the subject matter and was a motivating factor for this study. One main research question was considered in this study and it was: “What role did foreign intervention play in mediating the relationship between the Sikh genocide of 1984 and the state of the Indian nation?”. To answer these questions, a content analysis of media reports on the subject matter was used as the primary method of data collection which was complemented by in-depth interviews of key stakeholders. The findings of this study showed an insignificant intervention (positive or negative) during the period and issue under review. It was recommended that the international community, including Amnesty International, need to do more to prevent the proliferation of arms into crisis-prone areas and to also support these affected communities by providing humanitarian aid to them.